Teacher’s Competence in Teaching Filipino: A Concurrent Analysis Using Mixed-Methods Approach - Balbuena, Juvelyn J.; Napil, Melissa C. (Journal of Natural Language and Linguistics, 2025)
This study generally aims to understand Filipino teachers’ perspectives on the relationship between digital literacy, self-efficacy, and teaching competence. This serves as the basis for the study “Teacher’s Competence in Teaching Filipino: A Concurrent Analysis Using Mixed-Methods Approach” The study employs a mixed-methods approach, incorporating both quantitative and qualitative. A total of 400 participants were chosen through the use of a random sampling technique. The mean and Pearson product correlation were used in the data analysis. The results from the quantitative and qualitative data were also compared using the convergent parallel design. For the selection of participants for the in-depth interviews and focus group discussions, the researchers used purposive sampling. The study found a significant relationship between digital literacy, self-efficacy, and the teaching competence of Filipino teachers. Both exogenous and endogenous variables obtained an overall very high level. Common themes emerged from the participants’ opinions on the contribution of digital literacy and self-efficacy to teaching competency, highlighting the significance of utilizing these traits to improve Filipino teachers’ Self-Efficacy in the classroom. Achieving the very high level of overall description in terms of digital literacy and self-efficacy is crucial for the growth of Filipino teachers’ teaching competency.